Effect of Interest, Motivation, and Socio-Economic status on Student Decisions to Choose Bachelor Program Management - Jumadiah Wardati; Jopinus Ramli Saragih; Pinondang Hotria Siregar; Ricard Fredik Marpaung (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2018)
This study aims to determine the effect of Interest, Motivation, and Socio-Economic Status on Student Decisions Choosing a Bachelor of Management Program. The research method is quantitative data type and has primary data source with technical data collection by questionnaire. The population in this study amounted to 2,308 students. This study took a sample of 96 students using the Stratified Random Sampling method. Analysis of the data used is the Instrument Test, Classical Assumption Test, Hypothesis Test and Multiple Linear Regression obtained by the equation Y = 8.780 + 0.077X1 + 0.274X2 + 0.249X3. The results of the study indicate that: (1) Interest does not have no effect on the decision of students to choose the S-1 Management Program with a value of tcount (1,210) <ttabel (1,986); (2) Motivation influences students' decision to choose the S-1 Management Program with a tcount (3.959)> t table (1,986); (3) Socio-Economic Status influences the decision of students to choose the S-1 Management Program with a tcount (2,415)> t table (1,986); (4) Interests, Motivation and Socio-Economic Status jointly influence the decision of students to choose the S-1 Management Program with Fcount (11.903)> Ftable (2.70); (5) The student's decision variable choosing the S-1 Management Program is influenced by the variables of interest, motivation, and socio-economic status of 25.6% which are seen from the R2 value of 0.256. While the remaining 74.4% is influenced by other variables outside the research model, for example location variables, tuition fees, and facilities.